Larva of Rhynchophorus palmarum L. (Coleoptera: Curculionidae): Effect of diet on the synthesis of essential fatty acids - Maceda Santivañez, Julio Cesar; Chañi Paucar, Larry Oscar (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2021)
Insects are an important source of proteins, vitamins, amino acids, minerals, and lipids. In this context, the present study evaluated the essential fatty acid profile of the larval oil of Rhynchophorus palmarum (Coleoptera: Curculionidae) subjected to three plant tissue diets: Mauritia flexuosa (Arecaceae), Oenocarpus bataua (Arecaceae), and Jacaratia digitata (Caricaceae). Five adult individuals, 2 males, and 3 females were captured for their reproduction in captivity. The hatched larvae were subjected to the three diets for 45 days. After this period, extraction was carried out and the fatty acid profile of the oil was determined. Being oleic monounsaturated fatty acid (18:1) and palmitic saturated fatty acid (16:0), which are found in greater abundance for the three diets. Regarding essential fatty acids, linoleic (18:2) and alpha-linolenic (18:3) fatty acids were detected in concentrations of 1.96 ± 0.028 and 1.14 ± 0.007%, for the diet of Mauritia flexuosa, 0.67 ± 0.007 and 0.43 ± 0.035%, for the diet of Oenocarpus bataua, and 0.76 ± 0.000 and 0.29 ± 0.007%, for the diet of Jacaratia digitata, respectively. The results show that diets influence the type of fatty acid metabolized and its concentration. The larva is a source of monounsaturated fatty acids such as oleic (omega 9) and palmitoleic (omega 7) and of the essential fatty acids linoleic and alpha-linolenic precursors of the fatty acids of the omega 6 and omega 3 families.